Early real-world experience with emicizumab and concomitant factor VIII replacement products in adult males with Hemophilia A without inhibitors. (31st December 2022) - Cafuir, Lorraine; Estrin, Adina; Chen, Er; Hinds, David; Prince, Patricia; Thorburn, Jennifer; Mead, Henry; Kempton, Christine L.
Abstract: Aims: To assess real-world use of emicizumab in adult people with hemophilia A (PwHA) without inhibitors including healthcare resource utilization (HCRU) and costs. Materials and methods: Adult, male PwHA without inhibitors initiating emicizumab (index date) were identified using IBM MarketScan after 4 October 2016. Patients were required to have continuous health insurance coverage for ≥180 days prior to and ≥90 days after index date and have ≥90 days of continuous use of emicizumab. Patients were followed until treatment gap, disenrollment, or end of data. Results were reported overall and among a subgroup with prior factor VIII (FVIII) prophylaxis. Emicizumab use, concomitant FVIII treatment use, HCRU, and costs were assessed separately over baseline, the emicizumab induction period, emicizumab maintenance period, and annualized. Results: Among the 71 emicizumab patients (FVIII prophylaxis subgroup: 52) included in the study, the mean age was 35 (subgroup: 34) years and mean follow-up was 12 (subgroup: 11.1) months. At baseline, the annualized mean total healthcare cost was $532, 948 (subgroup: $645, 727). After emicizumab initiation, per-patient-per-month (PPPM) HCRU was higher in the emicizumab induction period compared to the maintenance period with higher monthly FVIII fills/in-office administrations (0.37 vs 0.17), non-FVIII outpatient visits (2.23 vs 1.55), and emergency department visits (0.06 vs 0.03). The FVIII prophylaxis subgroup yielded similar HCRU trends. Hemophilia treatment costs accounted for over 95% of total healthcare costs. The annualized mean cost was $50, 491 (subgroup: $61, 512) for concomitant FVIII treatment and $777, 171 (subgroup: $793, 168) for emicizumab and concomitant FVIII treatment for the first year of emicizumab treatment. Conclusion: This study represented experience with emicizumab after the approval for PwHA without inhibitors. The study cohort may not be representative of all PwHA taking emicizumab. The findings highlight the continued burden of treatment and healthcare cost for PwHA without inhibitors despite advances in treatment options.